Clinical and demographic differences between patients with manic, depressive and schizophrenia‐spectrum psychoses presenting to Early Intervention Services in London. Issue 3 (15th October 2017) - Kapila, Adisha; Fisher, Helen L.; Johnson, Sonia; Major, Barnaby; Rahaman, Nikola; Joyce, John; Chamberlain‐Kent, Nick; Lawrence, Jo; Young, Allan H.; Stone, James M.
Abstract : Aim: To investigate the relationship between the presenting clinical and demographic characteristics in first‐episode psychosis (FEP) patients with their clinical diagnostic grouping 1 year later. Methods: Data from 1014 first‐presentation psychosis patients from seven London‐based Early Intervention Services were extracted from the MiData audit database. Associations between clinical and demographic measures at presentation and clinical diagnosis made at 1 year were assessed with analysis of variance (ANOVA) and Chi‐square tests. Results: The sample comprised 76% of patients with schizophrenia‐spectrum diagnoses, 9% with manic psychoses (MP) and 6% with depressive psychoses. Compared to the other 2 groups, patients who were diagnosed as having MP were younger, with higher education and shorter duration of untreated psychosis, and had higher Young Mania Rating Scale scores at presentation and lower Positive and Negative Syndrome Scale (PANSS) negative scores. Patients diagnosed at 1 year as having depressive psychosis were older and more likely to be white, with the lowest PANSS positive scores at baseline. Patients diagnosed at 1 year as having schizophrenia spectrum diagnoses were more likely to be males. Patients in the 3 diagnostic subgroups of psychosis differed on both clinical and demographic characteristics at presentation. Conclusions: There were significant clinical and demographic differences at presentation between FEP patients who received different clinical diagnoses at 1 year. Future work should determine the extent to which these differences can be used to guide clinical care.